Tahap amalan pengurusan kurikulum sekolah rendah di Daerah Penampang Sabah : Satu kajian kes - Daynel, Petros (2010)
This research is a case study on curriculum management on 3 schools that was carried out in Penampang. A total of 46 currriculum managers (at school level) were involved in the evalution of curriculum management in the schools where the research had been carried out. The aim of this research is to check the implementation of the curriculum management in schools, to analyse the strength and weakness that occur in the curriculum management of school involved, to analyse and to see the correlation between curriculum management and academic performance of the school involved particularly in the UPSR Four hypothesis were formulated. The findings of this research are: there is a significant correlation between high level of curriculum management with high result in UPSR and moderate curriculum management with moderate UPSR result but there is no correlation between moderate level of curriculum management and poor result in UPSR. Among the weakness which occured in the curriculum management of those schools involved are: there are gaps of opinion between those who construct the curriculum and the implementer. There are weaknesses in dilivering the curriculum. A large class size hinders the implementation of the curriculum effectively, the restricted numbers of teachers, teachers with unsuitable options of teaching, the inproficiency of languages among students, and finally the behind schedule implementation of the computer laboratory facilities are the factors of weaknesses in curriculum management